2014
DOI: 10.1038/npp.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

Resting Brain Activity Varies with Dream Recall Frequency Between Subjects

Abstract: Dreaming is still poorly understood. Notably, its cerebral underpinning remains unclear. Neuropsychological studies have shown that lesions in the temporoparietal junction (TPJ) and/or the white matter of the medial prefrontal cortex (MPFC) lead to the global cessation of dream reports, suggesting that these regions of the default mode network have key roles in the dreaming process (forebrain 'dream-on' hypothesis). To test this hypothesis, we measured regional cerebral blood flow (rCBF) using [(15)O]H2O posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
109
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 74 publications
16
109
0
1
Order By: Relevance
“…Substantial change in DMN activity has been found to occur during the transitions from task states to the resting state687778. Moreover, recent studies have shown that DMN activity could be differentially modulated even in the absence of an external task157980. Taken together, our results demonstrate that the patterns of DMN topology vary across different brain states.…”
Section: Discussionsupporting
confidence: 68%
“…Substantial change in DMN activity has been found to occur during the transitions from task states to the resting state687778. Moreover, recent studies have shown that DMN activity could be differentially modulated even in the absence of an external task157980. Taken together, our results demonstrate that the patterns of DMN topology vary across different brain states.…”
Section: Discussionsupporting
confidence: 68%
“…This trait may be similar to that of individuals with high dream recall: in a recent study we showed that increased fast but decreased slow sleep spindles correlate with dream recall frequency [105]. The latter is a measure previously linked with higher reactivity to auditory stimuli both in wake and during sleep [148], and with increased activity in the temporoparietal junction and medial prefrontal cortex -areas typically associated with attention and memory [149]. This finding is consistent with observations in our current study: all our participants had high dream recall, and meditators had fewer slow sleep spindles than did non-meditating controls, possibly reflecting their increased alertness in sleep.…”
Section: Sleep Spindlessupporting
confidence: 52%
“…In another study, Eichenlaub et al, (2014) compared brain activity on those that recalled dreams more frequently (more than three times a week) with those that recalled dreams less frequently. The results showed that those that recalled dreams more frequently tended to be more reactive to external stimuli both during wakefulness and sleep.…”
Section: Dream Recallmentioning
confidence: 99%